Anisotropy of the T vs. H phase diagram and the HO/LMAFM phase boundary in URu2−xFexSi2 - Pouse, N.; Deng, Y.; Ran, S.; Graf, D.; Lai, Y.; Singleton, J.; Balakirev, F. F.; Baumbach, R. E.; Maple, M. B. (Frontiers in Electronic Materials, 2022)
The correlated f-electron compound URu2Si2 exhibits superconductivity (SC) with a critical temperature T_c = 1.5 K that coexists with the "hidden order" (HO) phase that forms below a characteristic temperature T_o = 17.5 K. The SC of URu2Si2 appears to be spin singlet chiral SC with d-wave order parameter symmetry, and the pairing of SCing electrons may involve spin excitations of the HO phase. Electrical resistance R measurements were performed on single crystal specimens of URu2-xFexSi2 with increasing x throughout the transition from the HO phase to the large moment antiferromagnetic LMAFM phase in high magnetic fields H oriented at various angles   theta with respect to the tetragonal c-axis. Measurements of R(theta) at H = 20, 33, 40, and 45 T were conducted in the temperature range 0.33 ≤ T ≤ 20 K and showed  theta-dependent behavior in the various phase transitions of URu2-xFexSi2 (HO, LMAFM, spin density wave, Fermi surface reconstruction, etc.). These phase transitions, as functions of T, H, and theta are plotted in a phase diagram of T vs. H||c = Hcos(theta)  for multiple values of x and show that H||c, not theta, is a tuning parameter of the URu2-xFexSi2 system throughout all Fe concentrations, as previously found by Scheerer et al. for the URu2Si2 parent compound.